2017
DOI: 10.1007/s11060-017-2589-3
|View full text |Cite
|
Sign up to set email alerts
|

SALL4 suppresses PTEN expression to promote glioma cell proliferation via PI3K/AKT signaling pathway

Abstract: Spalt-like transcription factor 4 (SALL4), a oncogene, is known to participate in multiple carcinomas, and is up-regulated in glioma. However, its actual role and underlying mechanisms in the development of glioma remain unclear. The present study explored the molecular functions of SALL4 in promoting cell proliferation in glioma. The expression level of SALL4 in 69 human glioma samples and six non-tumor brain tissues was determined using real-time polymerase chain reaction (PCR). Then, we transfected U87 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…Cell cycle analysis showed that the proportion of G1-phase cells was significantly increased, whereas the percentage of S-phase cells was significantly decreased with the increase ofAG1478 concentration. These results are consistent with previous reports [22][23][24], indicating that the main mechanism of action of AG1478 may be through its binding to EGFR, which then inhibits autophosphorylation, blocks EGFR-mediated signalling pathways, hinders cell cycle progression, inhibits cell proliferation and promotes apoptosis. The c-Myc protein, which has been proved to be an essential factor for cell proliferation, is also an accessory factor for reverse transcription that plays important roles in signal transduction, cell proliferation, differentiation, apoptosis and cell cycle control.…”
Section: Comparative Analysissupporting
confidence: 93%
“…Cell cycle analysis showed that the proportion of G1-phase cells was significantly increased, whereas the percentage of S-phase cells was significantly decreased with the increase ofAG1478 concentration. These results are consistent with previous reports [22][23][24], indicating that the main mechanism of action of AG1478 may be through its binding to EGFR, which then inhibits autophosphorylation, blocks EGFR-mediated signalling pathways, hinders cell cycle progression, inhibits cell proliferation and promotes apoptosis. The c-Myc protein, which has been proved to be an essential factor for cell proliferation, is also an accessory factor for reverse transcription that plays important roles in signal transduction, cell proliferation, differentiation, apoptosis and cell cycle control.…”
Section: Comparative Analysissupporting
confidence: 93%
“…This results in enhanced translation of a subset of genes that are required for protein synthesis, as well as acceleration of cell proliferation, which finally lead to tumorigenesis. [22][23][24] Previous studies report that polyamines are involved in the inhibition of AKT phosphorylation in colorectal cancer cells. 25 In addition, knockdown of AOC1 suppressed the EMT process in human gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, E3 ubiquitin-protein ligase regulated PTEN/PI3K/AKT signaling to promote the cell growth and migration of hepatocellular carcinoma cells (29). Liu et al (30) reported that Sal-like protein 4 suppressed PTEN expression to promote glioma cell proliferation via the PI3K/AKT pathway. Another study revealed that miRNA-1297 contributed to tumor growth of human breast cancer by targeting the PTEN/PI3K/AKT signaling pathway (28).…”
Section: Discussionmentioning
confidence: 99%